PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI PENYAJIAN DATA - Intan Dewi Ratih Sinamo; Rahmat Mushlihuddin; Nurhayani Hasibuan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The low learning outcomes of students in mathematics, particularly with regard to data presentation, serve as the basis for this study. Consequently, many students have not yet met the minimum competency criteria (KKM). The purpose of this study is to enhance the learning outcomes of fifth-grade students in Mathematics concerning the topic of data presentation through the implementation of the Problem Based Learning (PBL) model assisted by a statistical board. This research employed a classroom action research methodology, conducted over two cycles, encompassing planning, implementation, observation, and reflection. The planning phase involved designing instruction that considered students' characteristics to achieve the desired learning objectives. The implementation phase utilized the PBL model with the aid of a statistical board media. Observations were carried out to monitor students' progress during the learning process. Reflection activities were conducted to analyze the outcomes achieved by the students. The research findings indicate that the application of the PBL model assisted by a statistical board can improve the learning outcomes of students on the topic of data presentation. Students demonstrated an increased understanding of data presentation concepts in data collection and their ability to solve problems related to data presentation. This model gave students the chance to actively participate in their learning experience and see ideas in real-world contexts. These results imply that teaching data presentation to fifth-grade students using the PBL model with the help of a statistical board is a successful substitute method.